Correlation of pre‐operative circulating inflammatory cytokines with restenosis and rapid angiographic stenotic progression risk in coronary artery disease patients underwent percutaneous coronary intervention with drug‐eluting stents. Issue 3 (14th November 2019) - Sun, Jinling; Yu, Hui; Liu, Haining; Pu, Dongyu; Gao, Junhui; Jin, Xiaodong; Liu, Xiqiang; Yan, Aiguo
Abstract: Background: This study aimed to explore the associations of common inflammatory cytokine levels with restenosis and rapid angiographic stenotic progression (RASP) risk in coronary artery disease (CAD) patients underwent percutaneous coronary intervention (PCI) with drug‐eluting stents (DES). Methods: Two hundred and ten CAD patients underwent PCI with DES were consecutively recruited, then pre‐operative serum levels of TNF‐α, IL‐1β, IL‐4, IL‐6, IL‐8, IL‐10, IL‐17A, IL‐21, and IL‐23 were determined by ELISA. The 12‐month in‐stent restenosis and RASP of non‐intervened lesion were assessed by quantitative coronary angiography analysis. Results: The pre‐operative TNF‐α, IL‐6, IL‐17A, and IL‐23 expressions were increased while IL‐4 expression was decreased in restenosis patients compared with non‐restenosis patients. Further analysis revealed that IL‐6, IL‐8, hypercholesteremia, diabetes mellitus, and HsCRP could independently predict restenosis risk, and subsequent ROC curve revealed that their combination was able to differentiate restenosis patients from non‐restenosis patients with an AUC of 0.951 (95%CI: 0.925‐0.978). Meanwhile, the pre‐operative TNF‐α, IL‐6, IL‐17A, IL‐21, and IL‐23 expressions were increased whereas IL‐4 level was decreased in RASP patients compared with non‐RASP patients. Further analysis revealed that TNF‐α, IL‐6, IL‐23, hypercholesteremia, SUA, HsCRP, and multivessel artery lesions could independently predict RASP risk, and subsequent ROC curve disclosed that their combination could discriminate RASP patients from non‐RASP patients with an AUC of 0.886 (95%CI: 0.841‐0.931). Conclusions: This study unveils the potentiality of pre‐operative circulating inflammatory cytokines as markers for predicting restenosis and RASP risk in CAD patients underwent PCI with DES.